2019
DOI: 10.1109/rbme.2018.2874353
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Methods for Pulmonary Diagnosis

Abstract: Recent developments in sensor technology and computational analysis methods enable new strategies to measure and interpret lung acoustic signals that originate internally, such as breathing or vocal sounds, or are externally introduced, such as in chest percussion or airway insonification. A better understanding of these sounds has resulted in new instrumentation that allows for highly accurate as well as portable options for measurement in the hospital, in the clinic, and even at home. This review outlines in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 157 publications
(340 reference statements)
4
67
0
Order By: Relevance
“…The common types include crackles, wheezes, rhonchi, stridor, and squawks. A variety of lung pathologies and injuries result in adventitious respiratory sounds and/or alter sound transmission pathways, with both spectrally and regionally differing effects that, if properly quantified, may provide additional information about the severity and location of the trauma or disease [54]. For COVID-19, where there is currently an overall lack of clinical studies on respiratory sounds, a study has investigated lung sounds on patients with confirmed COVID-19 by lung auscultation, and shown that all patients (n=10) were found to have abnormal respiratory sounds [55].…”
Section: Lung Soundsmentioning
confidence: 99%
“…The common types include crackles, wheezes, rhonchi, stridor, and squawks. A variety of lung pathologies and injuries result in adventitious respiratory sounds and/or alter sound transmission pathways, with both spectrally and regionally differing effects that, if properly quantified, may provide additional information about the severity and location of the trauma or disease [54]. For COVID-19, where there is currently an overall lack of clinical studies on respiratory sounds, a study has investigated lung sounds on patients with confirmed COVID-19 by lung auscultation, and shown that all patients (n=10) were found to have abnormal respiratory sounds [55].…”
Section: Lung Soundsmentioning
confidence: 99%
“…Rao et al [ 19 ] discussed acoustic techniques for pulmonary analysis. They studied acoustic aspects for different lung diseases.…”
Section: Introductionmentioning
confidence: 99%
“…One of the urgent directions of sports medicine nowadays is an athlete's organism functional reserves increase on the basis of non-medicated (non-drug) technologies [1][2][3][4][5][6]. Such technologies include the technologies based on the influence of low-frequency vibrations on a person's respiratory system [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%